Peran Notaris dalam Pembuatan Perjanjian Pemutusan Hubungan Kerja Secara Sepakat antara Pengusaha dan Pekerja - Dita Riswuri Widyaningrum (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The termination of employment agreement by mutual consent is a form of agreement between an employer and an employee to end the employment relationship based on the will of both parties. This agreement has significant legal implications in ensuring workers' rights and preventing industrial disputes. This study aims to analyze the role of a notary in drafting mutual termination of employment agreements and the legal strength of notarial deeds as written evidence. The research method used is normative juridical with a statutory and conceptual approach. The results show that a notary plays an essential role in ensuring that agreements are made voluntarily, do not violate workers' rights, and comply with applicable laws and regulations. A notarial deed also provides stronger evidentiary power in the resolution of industrial disputes.